Adolescents' intention and self-efficacy to follow Pap testing recommendations after receiving the HPV vaccine. Issue 6 (2nd June 2016) - Higgins, Lisa M.; Dirksing, Kelsie N.; Ding, Lili; Morrow, Charlene D.; Widdice, Lea A.; Kahn, Jessica A.
ABSTRACT: Human papillomavirus (HPV) vaccines are recommended in the US for girls and women 11–26 y of age. Because these vaccines do not prevent all cervical cancers, Papanicolaou (Pap) screening is still recommended after vaccination. Young women who have been vaccinated may perceive themselves at lower risk for HPV infection and cervical cancer, which could lead to lower intention and self-efficacy to follow cervical cancer screening guidelines, and subsequent nonadherence to Pap testing. The aim of this study was to examine whether perceived risk of human papillomavirus (HPV) after vaccination and other factors are associated with adolescents' intention and self-efficacy to get Pap testing after HPV vaccination. Women 13–21 y of age (N = 339) receiving their first HPV vaccine dose completed a survey. Multivariable logistic regression examined associations between perceived risk of HPV and intention/self-efficacy to get a Pap test while adjusting for other factors. Approximately half of participants reported high intention and half reported high self-efficacy to get a Pap test. Factors significantly associated with high intention were Pap testing history and knowledge about HPV/HPV vaccines; factors significantly associated with high self-efficacy included insurance plan, Pap testing history, communication with clinician about needing a Pap test after vaccination, lifetime number of male sexual partners, and recent smoking. In conclusion, educating adolescents about HPV/HPV vaccines and the need for Pap testing may increase self-efficacy/intention to get a Pap test after vaccination.